Awareness of FO Employees on Environmental Management System (EMS) at Hotel Le Meridien Bali Jimbaran - Ni Luh Evi Cahyani Putri; I Ketut Suarja; Ni Ketut Bagiastuti; Elvira Septevany (Journal of Management and Business Environment (JMBE), 2023)
This study aims to know the implementation of the environmental management system (EMS) and determine the relationship of awareness of EMS and imlementation of EMS of the front office department at Hotel Le Meridien Bali Jimbaran. The data collection methods of this research were observation and questionnaire. The sampling technique in used was the saturated sampling technique with a total sample of 35 respondents. Data was collected using online questionnaires distributed to the respondents using QR barcodes. The questionnaire data were processed with the help of SPSS 25 software for windows. The data analysis technique uses frequency, mean, and standard deviation. In addition, correlation analysis technique was used to determine how far the front office employee awareness relates to EMS implementation. The results show that implementing EMS in the front office department was maximal. The correlation analysis results in employee awareness and the implementation of EMS in the front office department is moderate. The need to improve awareness of the front office department is thus considerably important